2019
DOI: 10.3390/ma13010059
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Microstructure of Class-C Fly Ash and GGBS Blend Geopolymer Activated in NaOH & NaOH + Na2SiO3

Abstract: In this paper, class-C fly ash (FA) and ground granulated blast-furnace slag (GGBS)-based geopolymer activated in NaOH and NaOH + Na 2 SiO 3 was studied regarding setting time, compressive strength, porosity, microstructure, and formation of crystalline phases. When comparing the effects of alkali type on the FA and GGBS geopolymer composites, results revealed that NaOH has a lesser effect in developing strength and denser microstructure than does NaOH + Na 2 SiO 3, since the addition of Na 2 SiO 3 provides th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 42 publications
(74 reference statements)
5
21
0
Order By: Relevance
“…The binary binder CS2 showed the formation of mainly C-A-S-H and C-S-H binding phases (with C 4 AlH 13 compound having a lower aluminum content of 3.6%) due to the higher calcium content in the system, owing to the composition of reagent 2 (Figure 15b). Similar binding phases/gels were characterized in recent studies on fly ash and slag-based pastes/mortars [57,58,71]. This additional C-S-H gel formation further densified the microstructure and improved compressive strength compared to binder CS1.…”
Section: Microstructural Analysissupporting
confidence: 71%
“…The binary binder CS2 showed the formation of mainly C-A-S-H and C-S-H binding phases (with C 4 AlH 13 compound having a lower aluminum content of 3.6%) due to the higher calcium content in the system, owing to the composition of reagent 2 (Figure 15b). Similar binding phases/gels were characterized in recent studies on fly ash and slag-based pastes/mortars [57,58,71]. This additional C-S-H gel formation further densified the microstructure and improved compressive strength compared to binder CS1.…”
Section: Microstructural Analysissupporting
confidence: 71%
“…Sodium silicate “Na 2 SiO 3 ” and sodium hydroxide “NaOH” are two common activators, either combined (in a certain ratio) or used individually to manufacture geopolymer-type binders [ 4 , 5 ]. It is reported that, Na 2 SiO 3 , when incorporated in NaOH solution, shows promising results in improving the mechanical properties of activated precursors compared to only NaOH-activated precursors [ 3 , 6 ]. Generally, NaOH works as a mineralizer, which breaks the covalent bonds present in the aluminosilicate precursor material(s), therefore, releasingthe Si and Al into the system [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given that the research on a waste glass-based alkali activator is limited and no research has been conducted on the influence of this activator on the properties of high calcium (Ca) alkali-activated material (AAM), it suggests that the research reported here is warranted. Class-C FA and GGBS composed of high Ca was selected for our previous study [ 6 ]. It was determined that the Class-C FA compared to GGBS is less reactive when activated by NaOH-4M solution, but when these materials were activated by NaOH+Na 2 SiO 3 solution, the dissolution of FA and GGBS was enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…Fly-ash based geopolymer concretes have been synthesised from different power stations, resulting in substantially different particle size, morphology, and composition due to the different coal powders and combustion conditions in those plants [ 2 , 30 , 33 , 34 , 35 , 36 , 37 , 38 ]. Fly-ash is excellent for improving early strength and durability, rendering it suitable as the primary source materials in the synthesis of geopolymer concrete [ 2 , 33 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%